Experimental study on the performance of CFRP-strengthened masonry structures under debris flow impacts. (June 2021) - Li, Peizhen; Xu, Shiran; Lu, Zheng; Li, Jin
Abstract: This paper takes common masonry structures built in mountainous areas prone to debris flow as a research object and proposes carbon fiber-reinforced polymer (CFRP) to improve the resistance of the structures under debris flow impacts. According to a series of impact loading tests on an unreinforced model (hereinafter referred to as UM) and a CFRP-strengthened model (hereinafter referred to as CM), dynamic responses and failure mechanisms of these two structures under debris flow impacts are analyzed. To simulate the impact of large boulders in debris flows, steel balls with different diameters are placed on a loading device, and they roll down along the track from different heights to input homologous impact energy to the scaled models. The test results reveal that the maximum peak acceleration of the CM is only 51.3% of that of the UM, and the peak displacement of the CM is 50% of that of the UM, while the residual displacement is 65% of that of the UM (under the loading case G6 in this paper). When the models reach the serviceability limit state (defined in this paper), the absorbed impact energy of the CM is 7.35 times that of the UM. The test results show that CFRP is an effective reinforcement material to significantly improve structural bearing capacity and reduce dynamic response of structures under debris flow impacts. This study will be helpful for building construction and reinforcement in mountainous areas prone to debris flow impact.